A republican account of the value of privacy. (July 2015) - Roberts, Andrew
This article provides an account of the value of privacy in securing the republican aims of self-government and conditions of non-domination. It describes how loss of privacy might lead to subjugation to dominating power. The republican concept of domination provides the foundation of a broad and coherent account of the value of privacy. One that encompasses circumstances in which the subject (i) suffers interference as a result of the loss, (ii) is aware that he has suffered a loss of privacy, but suffers no subsequent interference and (iii) is unaware that he has suffered any loss of privacy, and suffers no subsequent interference. Liberal accounts explain the value of privacy in the first two circumstances by pointing to the possible effect of the loss on the autonomy of the subject, but because they focus on autonomy are unable to explain why privacy is valuable where an agent is unaware of the loss. The republican account provided here explains why loss is harmful in all three circumstances. The final part of the article argues that because privacy is a pre-requisite for effective participation in political life, and republicans consider such participation to be the essence of self-government and the means through which a polity can secure conditions of freedom, in a republican democracy individual privacy will be seen as a collective good.